Derajat Aglutinasi Pemeriksaan Golongan Darah Metode Cell Grouping Berdasarkan Tingkat Konsentrasi Suspensi Sel - Nur Muhjah Khoolidah; Nurul Qomariyah (Poltekkes Kemenkes Semarang, 2019)
Blood transfusions must go through of strict procedures to prevent transfusion reactions that can appeared. One procedure that must be do is the examination of ABO and Rhesus blood group. Ratio of antigens and antibodies play a role in the formation of agglutination. The more bonded antigens-antibodies, the larger, clearer, and stronger the agglutination will be. Analyzing the different of degree of agglutination of blood examination cell grouping method based on cell suspension concentration level. The type of research used is experimental research. The subjects of the study were 18 college students were grouped by blood group A, B and AB. Each cell specimen was treated to make cell suspension concentration of 5%, 10%, 15% and 20%. All examination result show degree of agglutination 4+. The cell suspension concentration of 5%, 10%, 15% and 20% in blood type A and B examination show the same data that’s degree of agglutination 4+ with clear background. The cell suspension concentration of 5 in blood type AB examination show degree of agglutination 4+ with clear background of 70%.